Nontoxic and renewable metal–organic framework based on α-cyclodextrin with efficient drug delivery. Issue 86 (2nd September 2016) - Sha, Jing-Quan; Zhong, Xiao-Hua; Wu, Lian-He; Liu, Guo-Dong; Sheng, Ning
Abstract : Two new nontoxic α-CD based compounds were synthesized by different method, which contain different left-handed helix and exhibit efficient drug loading capacity and sustained release behaviors. Abstract : A novel α-cyclodextrin based metal–organic framework (CD-MOF) with chiral helices, K3 (C36 H60 O30 )2 ·7H2 O (1 ), was synthesized by vapor diffusion method, which contains infinitely long left-handed helical chains, interdigitated with six circumambient helical chains. Compound1 exhibits efficient drug loading capacity and excellent sustained release behavior. In addition, by changing the synthetic method, another compound based on α-cyclodextrin, (C36 H60 O30 )·H2 O (2 ), was isolated by solvothermal synthesis, which contains left-handed chiral helical double channels, linked with adjacent four same helical channels. Moreover, the lower cytotoxicity of the two compounds indicates that they are a type of renewable, environmentally friendly and biocompatible drug carrier material.